2015
DOI: 10.1016/j.matdes.2015.07.074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment and Fe content on the microstructure and mechanical properties of die-cast Al–Si–Cu alloys

Abstract: The effect of solution and ageing heat treatment on the microstructure and mechanical properties of the die-cast Al-9 wt.%Si-3.5 wt.%Cu alloys containing 0.1-1.0 wt.% Fe was investigated. The results showed that the dendritic primary α-Al phase was varied from 20 to 100 μm in size and the globular α-Al grains were smaller than 10 μm in size. The Fe-rich intermetallics exhibited coarse compact or star-like shapes with the sizes from 10 to 20 μm and the fine compact particles at an average size of 0.75 μm. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…Therefore, a soft alloy matrix (such as ductile Al-Mg matrix) is necessary for high-Fe alloy. On the other side, it was found that Fe-rich phases in aluminium alloys are helpful in improving the yield strength with the scarification of ductility [8]. Besides, the addition of Mn in Al-Mg alloys can modify Al3Fe to Al6(Fe, Mn), and the increased cooling rate can significantly refine the Al6(Fe, Mn) phase.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a soft alloy matrix (such as ductile Al-Mg matrix) is necessary for high-Fe alloy. On the other side, it was found that Fe-rich phases in aluminium alloys are helpful in improving the yield strength with the scarification of ductility [8]. Besides, the addition of Mn in Al-Mg alloys can modify Al3Fe to Al6(Fe, Mn), and the increased cooling rate can significantly refine the Al6(Fe, Mn) phase.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Al-Si cast alloys are commonly used materials for automotive engine components, as reported in [3][4][5][6]. However, the manufacturing process, as well as the subsequent heat treatments, must be considered as they possess distinctive impacts on the resulting mechanical properties [7][8][9]. As such cast aluminum components are also exposed to elevated temperatures during service, the characterization of the material properties under these conditions is inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…Iron addition was significant for further improving the tribological characteristics of the alloy. But nowadays standard alloys include in small quantities most of the elements mentioned above [7]. A combination of all these elements helps in changing the structure of the primary and eutectic Silicon from coarse needle like of plate to a globular form.…”
Section: Introductionmentioning
confidence: 99%